1977
DOI: 10.1111/j.1365-3180.1977.tb00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of shattercane seed in soil across Nebraska*

Abstract: Summary: Longevity of shattercane [Sorghum bicolor (L.) Moench] seed buried 22 cm deep in soil at three locations across Nebraska, U.S.A. was followed for 14 years. Shattercane seed lost viability more quickly when buried in a Keith very fine sandy loam in western Nebraska (Alliance, average seed germination 21%) than in a Holdrege silt loam in central (North Platte, 37% germination) or in a Sharpsburg silty clay loam in eastern Nebraska (Lincoln, 38% germination) which were similar. The maximum survival of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…It must be remembered that the beads declined slightly more rapidly with time at Long Ashton but, even when this was taken into account, there was a faster decline rate for a number of species, including C. fontanum , C. album , F. officinalis , G. aparine and P. aviculare. Burnside et al . (1977) have also reported higher decline rates for seeds of Sorghum bicolor (L.) Moench in lighter soils but, surprisingly, there seem to be few other published reports on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…It must be remembered that the beads declined slightly more rapidly with time at Long Ashton but, even when this was taken into account, there was a faster decline rate for a number of species, including C. fontanum , C. album , F. officinalis , G. aparine and P. aviculare. Burnside et al . (1977) have also reported higher decline rates for seeds of Sorghum bicolor (L.) Moench in lighter soils but, surprisingly, there seem to be few other published reports on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Robert [40], Robert and Feast [41] also observed that weed seeds in shallow soil layers or exhumation of the buried seeds to the shallow layers increase the chances of mortality of the weed seeds as compared to the deeper ones. Actually, the burial of weed seeds in deeper layers provide more or less constant soil conditions, and longevity of these seeds may be more closely related to the adaptations by the seeds to this condition itself [42].…”
Section: Crop Establishment Methodsmentioning
confidence: 99%
“…It can grow to a height of 1-3 m and produce over 1000 seeds per panicle. Seeds on mature panicles may shatter before the crop is harvested and can remain viable for up to 13 years when buried in soil (Burnside et al 1997). Shatter cane can vigorously compete with all crops for light, nutrients, and water (Burnside 1990;Fellows & Roeth 1992).…”
Section: Introductionmentioning
confidence: 99%